Indirect somatic embryogenesis of Agave maximiliana Baker - Delgado-Aceves, Lourdes; Corona, Santiago; Castañeda-Nava, José Juvencio; Rodríguez-Domínguez, José Manuel; Gutiérrez-Mora, Antonia (Frontiers in Plant Science, 2025)
Agave maximiliana Baker is a key species in the production of the traditional mexican beverage “Raicilla”. However, its slow reproductive cycle, lack of vegetative propagation, and increased commercial exploitation pose a threat to the conservation of its natural populations. This study presents, for the first time, a protocol for indirect somatic embryogenesis from zygotic embryos of A. maximiliana, as a biotechnological strategy for its mass propagation and conservation. Mature seeds were collected, and their viability was assessed using tetrazolium staining, revealing a significant loss of viability in seeds stored for more than two years. Embryonic axes were cultured on Murashige and Skoog medium supplemented with different concentrations of 2,4-D or picloram in combination with BAP. The highest embryogenic callus formation rates (up to 90%) were obtained with the treatment consisting of 36.24 µM 2,4-D, 33.12 µM picloram, and 4.44 µM BAP, resulting in an embryo-forming capacity (EFC) of 20%. Histological analyses confirmed the presence of proembryogenic cell masses and somatic embryos at different developmental stages, indicating an asynchronous regenerative system. The conversion rate of embryos into viable plantlets reached up to 90%, although some abnormalities were observed, associated with high auxin concentrations. This protocol represents a valuable tool for the conservation, reforestation, and sustainable production of this endemic and economically important species.